2016
DOI: 10.1080/13685538.2016.1195361
|View full text |Cite
|
Sign up to set email alerts
|

Impact of combination therapy 5-alpha reductase inhibitors (5-ARI) plus alpha-blockers (AB) on erectile dysfunction and decrease of libido in patients with LUTS/BPH: a systematic review with meta-analysis

Abstract: Lower urinary tract symptoms (LUTS) secondary to benign prostatic obstruction (BPO) represent one of the most common clinical complaints in adult men. Several drugs used for LUTS/BPO may strongly affect sexual function and bother. The aim of this systematic review and meta-analysis was to evaluate the impact of combination therapy with alpha-blockers (AB), 5-alpha reductase inhibitors (5-ARI) on the risk of erectile dysfunction(ED) and libido alterations (LA) from randomized clinical trial (RCT). Based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 26 publications
1
13
2
3
Order By: Relevance
“…Generally, the incidence of libido‐related SexAEs in patients on 5ARIs is low. In fact, in a previous study, the risk of libido alteration was comparable for both patients treated with 5ARI monotherapy and those treated with combination therapy . Therefore, in this study, the MSHQ tool did not correlate well with libido‐related SexAEs.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Generally, the incidence of libido‐related SexAEs in patients on 5ARIs is low. In fact, in a previous study, the risk of libido alteration was comparable for both patients treated with 5ARI monotherapy and those treated with combination therapy . Therefore, in this study, the MSHQ tool did not correlate well with libido‐related SexAEs.…”
Section: Discussioncontrasting
confidence: 72%
“…Generally, the incidence of libido-related SexAEs in patients on 5ARIs is low. In fact, in a previous study, the risk of libido alteration was comparable for both patients treated with 5ARI monotherapy and those treated with combination therapy 16. Therefore, in this study, the MSHQ tool did not correlate well with libido-related SexAEs.Our observation of a clear discrepancy between the directionality of MSHQ sexual desire (libido) domain scores and the likelihood of patients reporting libido-related SexAE is thought-provoking.…”
contrasting
confidence: 72%
“…However, the potential for sexual dysfunction with 5ARI‐α 1 ‐blocker combination therapies can limit their use in clinical practice, despite patient satisfaction with treatment and clinical studies indicating efficacy in reducing symptoms, clinical progression, and the risk of surgery . A systematic review and meta‐analysis revealed that erectile dysfunction (ED) and libido alteration were notably more prevalent in patients treated with combination therapy compared with those treated with α 1‐ blocker monotherapy alone . The risk of ED was higher in those treated with combination therapy but the risk of libido alteration was the same for both patients treated with 5ARI monotherapy and those treated with combination therapy …”
Section: Introductionmentioning
confidence: 99%
“…A systematic review and meta‐analysis revealed that erectile dysfunction (ED) and libido alteration were notably more prevalent in patients treated with combination therapy compared with those treated with α 1‐ blocker monotherapy alone . The risk of ED was higher in those treated with combination therapy but the risk of libido alteration was the same for both patients treated with 5ARI monotherapy and those treated with combination therapy …”
Section: Introductionmentioning
confidence: 99%
“…Whereby, several drug combinations, such as ABs and 5alpha reductase inhibitors (5ARIs), have been well established and are currently reported in the major urological guidelines as standard therapies. However, despite their efficacy in treating LUTS, their side effects, above all on sexual function, are mainly detrimental [ 2 , 38 ••, 40 42 ].…”
Section: Discussionmentioning
confidence: 99%